Comportamento de ligações aço-concreto reciclado por meio de adesivos - Andrade Filho, Paulo Eduardo Soares (2021)
In a steel-concrete composite members, it’s essential that there is a connection between the materials so that there is a joint behavior that makes them capable of jointly resisting the solicitant efforts. To do this, they are usually connected by mechanical devices such as stud bolts connectors. However, this type of connection has some problems such as the concentration of shear stresses at the interface, and the need for welding that introduces residual stresses and degrades the steel. Therefore, in the last two decades, studies have evaluated adhesive bonding as a possible bonding alternative for composite steel-concrete elements, especially in composite beams. Simultaneously, research about the use of concrete with aggregates of concrete waste has been carried out to alleviate the impact of civil construction on the environment. There is a need to reduce the extraction of natural resources and minimize the volume of solid waste from this sector that is discarded. Thus, the objective of the present work was to analyze the behavior of the steel-concrete adhesive bond made with epoxy adhesive and whose concrete contains recycled concrete aggregate (RAC). Through push-out tests, the influence of the thickness of the adhesive on the bond and the type of concrete (natural aggregates or RAC) was evaluated. Specimens with steel-epoxy-steel and steel-epoxy-concrete connections were evaluated by means of push-out tests using the following variables: adhesive thicknesses of 1 mm and 3 mm and replacement contents of 30% and 100% of the coarse aggregate natural by ARC. The results showed a direct relationship between the increase in adhesive thickness and the shear bond strength for both bonds: steel-epoxy-steel and steel-epoxy-concrete. Regarding the use of RCA in concrete, no significant difference was observed in the results of the ANOVA analysis of variance, however there was a trend towards a reduction in the bond strength with the use of RCA. Finally, the steel-concrete adhesive bonding showed to have an adequate behavior for use in composite steel-concrete elements, mainly because it considerably reduces the relative displacements between the materials.